The role of metacognitives behaviors in solving mathematical problem - Mohamed, Mohini (Faculty of Education, 2007)
This research is a qualitative study on the metacognitive behaviours in the process o f solving mathematical problems. A case study was used to identify the understanding and to determine the type and pattern of metacognitive behaviours and the associated achievement in mathematical problem solving. Four Form Four students are used as samples in tackling the mathematical problems using De Corte ( 2003 ) model. The various phases of De Corte model are as follows : build a mental representation o f the problem, decide how to solve the problem, execute the necessary calculations, interpret the outcome and formulate an answer and evaluate the solution , all o f which are focused on metacognitive aspect. At the same time, problems faced by the students when showing the metacognitive behaviours during the process of solving problem are also identified Data has been collected through verbatim protocol while students undergoing the thinking aloud process in solving three mathematical problems. Methods such as retrospective interview, observation, reviewing of written answers of students were used as the supporting data in this study.